2021
DOI: 10.1177/23779608211038204
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Ghanaian Midwives on the Use of Nonadjustable Delivery Beds: A Qualitative Study

Abstract: Background Hospital beds are of great assistance to both clients and caregivers as they give lots of choices to the users. More often, clients have difficulty getting in and out of beds, but the adjustable features of the beds make it possible for them to be comfortable, regardless of their condition. This situation may not be the same if nonadjustable delivery beds (NADBs) are used in conducting deliveries at health care facilities. This study explored the experiences of midwives using NADBs in selected Chris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…On predisposing factors, the results of this study showed that poor body posture and unavailability of Non-Adjustable Delivery Beds (NADBs) were significant predisposing factors for work-related musculoskeletal disorders. This result is consistent with the earlier reports, wherein the unavailability of adjustable beds and poor body posture as significant risk factors for work-related musculoskeletal disorders [ 7 , [17] , [18] , [19] , [20] ]. The possible explanation for the above findings is that working in an awkward posture puts stress on the muscles, bones, and joints.…”
Section: Discussionsupporting
confidence: 93%
“…On predisposing factors, the results of this study showed that poor body posture and unavailability of Non-Adjustable Delivery Beds (NADBs) were significant predisposing factors for work-related musculoskeletal disorders. This result is consistent with the earlier reports, wherein the unavailability of adjustable beds and poor body posture as significant risk factors for work-related musculoskeletal disorders [ 7 , [17] , [18] , [19] , [20] ]. The possible explanation for the above findings is that working in an awkward posture puts stress on the muscles, bones, and joints.…”
Section: Discussionsupporting
confidence: 93%
“…The midwives adopted strategies such as calling for help and borrowing oxygen from other wards to resuscitate the patients ( Dartey et al, 2021 ; Ismaila et al, 2021 ). It is also interesting to note that some midwives, despite the challenges involved in peer monitoring and supervision, readiness to learn new ways of solving existing problems.…”
Section: Discussionmentioning
confidence: 99%
“…No new ideas, concepts and themes were emerging after the 12th to 15th nurses were interviewed, hence data collection was stopped. 2022 Registered nurses at the rank of Senior Staff Nurses (SSN) and above, with at least three (3) years of experience handling children with burn injuries at the time of data collection, were included in this study. This ensured that contributions were more in-depth and rich because they came from people with greater knowledge about the burn’s environs.…”
Section: Methodsmentioning
confidence: 99%